(untitled) - Estève, Jean (Rome, Italy, 2005)
This Code draws upon the FAO Model Code of Forest Harvesting Practice of 1996 and is driven by the fundamental principle that it is possible to conduct forest harvesting operations in ways that significantly reduce negative impact. It focuses primarily: on the African region in the broad sense, encompassing the tropical countries of West and Central Africa; on timber harvesting because of its potential damage on environment; and on closed natural production moist forests, although some of the guidelines also apply to protection and plantation forests.
Keywords: Forest management,Quản lý rừng; Tropics,Vùng nhiệt đới